TINJAUAN YURIDIS TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA JENIS SABU - KARINA OCTAVIA SEMBIRING; BAYU FAHRURAJI PUTRA; RAHMAYANTI Rahmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
The problem of narcotics crime has become a very serious problem. mental, emotional, and behaving in society. Criminal law policy in viewing perpetrators of narcotics abuse as victims, but field data shows that almost 99% of judges' decisions are still in prison terms. Regarding this journal, it explains the problem of how the application of criminal law concerning the regulation of criminal acts of narcotics generally of the type of methamphetamine in Indonesia. The research method in this journal is done by a normative juridical approach.